UWB antenna based time-domain approach for through the walls gap estimation - Shaikh, Faraz Ahmed; Khan, Sheroz; Alam, A. H. M. Zahirul; Habaebi, Mohamed Hadi; Baillargeat, Dominique; Kadir, Kushsairy Abdul; Shah, Jawad Ali; Shahid, Zeeshan; Yahya, Muhammad (IEEE, 2019)
This paper has introduced a novel experimental system adopted a time domain approach for estimating through wall distance and recognizes buried objects behind the wall. The designed and fabricated balanced antipodal Vivaldi antenna (BAVA) has been used for the development of UWB system. The working mechanism of an intended detection system based on time domain reflectometry (TDR) and ground-penetrating radar (GPR). A miniature pulse in the UWB range is generated by the vector network analyzer (VNA) to irradiate a barrier made of two walls separated by airgap between them. The signal radiations reflect partially from the front wall while remaining goes through for getting reflected from the rear wall. The VNA is used for measuring the time interval passed between the instant when an incident signal irradiates the first wall and the instant when the incident signal gets reflected from the rear wall. The investigational process of a system is carried out by UWB antenna probe. The detected information is attained using the values of reflection coefficient (S 11 ) represented in time domain measurements. Experimental results have been proved the ability to detect wall gap as well as the width estimation between two walls with high accuracy. The maximum percentage error has been found to not exceeding 4.5% in the worst condition.